Embracing context and complexity to address environmental challenges in the water-energy-food nexus. (October 2020) - Larkin, A.; Hoolohan, C.; McLachlan, C.
Highlights: We present a novel method for socio-technical scenario analysis for the water-energy-food nexus. It enables participants to embrace complexity and multidimensionality of changes across the nexus. The method allows participants to imagine radically different future configurations of socio-technological systems. This challenges assumptions that favour technological solutions over those that require change to lifestyles and governance. The findings support the use of qualitative, participatory scenario analysis in decision-making. Abstract: Wicked environmental challenges require far-reaching changes to social, economic and technical systems. Yet, dominant ways of assessing how to mitigate global environmental change are highly reductive in their treatment of uncertainty and multidimensionality in these systems. Their common focus on optimal solutions, derived from quantitative techno-economic models, downplays social, geographical and political factors that influence the direction and pace of change. Taking a transdisciplinary approach and using a water-energy-food nexus framing, we demonstrate how participatory scenario analysis can assist stakeholders in articulating why many technologically-focused solutions to complex environmental challenges fail to achieve their intended goals, and how alternative solutions that recognise uncertainty and interdependency can be up-scaled. The findings illustrate the critical importance of changing social, geographical and governance conditions for innovation. The participatory method enables stakeholders to examine the implications of possible future changes and to navigate emergent difficulties and opportunities so that environmental challenges can be addressed effectively. The method allows participants to imagine radically different configurations of socio-technological systems, and examine their feasibility in a manner that challenges the current paradigm in which technologies are more feasible, effective and politically acceptable solutions to global societal challenges than those requiring changes to lifestyles and governance.